Incremental effects of facemask therapy associated with intermaxillary mechanics - Thiesen Guilherme; Fontes Juliana de Oliveira da Luz; Zastrow Michella Dinah; May Naudy Brodbeck (Sciendo, 2023)
To determine the dentofacial changes in children with skeletal Class III malocclusions treated with maxillary expansion, external maxillary protraction and intermaxillary traction.